2021
DOI: 10.3389/fonc.2021.759509
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-Term and Perioperative Outcomes of Robotic Versus Conventional Laparoscopic Gastrectomy for Gastric Cancer: A Systematic Review and Meta-Analysis of PSM and RCT Studies

Abstract: BackgroundTo investigate the perioperative and oncological outcomes of gastric cancer (GC) after robotic versus laparoscopic gastrectomy (RG versus LG), we carried out a meta-analysis of propensity score matching (PSM) studies and randomized controlled study (RCT) to compare the safety and overall effect of RG to LG for patients with GC.MethodsPubMed, Web of Science, EMBASE, and Cochrane Central Register were searched based on a defined search strategy to identify eligible PSM and RCT studies before July 2021.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(64 citation statements)
references
References 39 publications
1
62
1
Order By: Relevance
“…Although robotic surgery is considered to be superior to laparoscopy in several disciplines, including colorectal, gastric, pancreatic, gynecological, and urological procedures, there are some controversies about the safety and efficacy of RPD compared with LPD (23)(24)(25)(26)(27). In order to explore the real efficacy of RPD, this meta-analysis included relevant studies from 2016 to 2021 to explore the safety and effectiveness of RPD and LPD.…”
Section: Discussionmentioning
confidence: 99%
“…Although robotic surgery is considered to be superior to laparoscopy in several disciplines, including colorectal, gastric, pancreatic, gynecological, and urological procedures, there are some controversies about the safety and efficacy of RPD compared with LPD (23)(24)(25)(26)(27). In order to explore the real efficacy of RPD, this meta-analysis included relevant studies from 2016 to 2021 to explore the safety and effectiveness of RPD and LPD.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis involved all 224 studies: out of them, 193 ones turned as not relevant for title and abstract, while 31 full-texts were considered eligible. Twe of the 31 studies were excluded because they were identified as duplicate publicati After removal of 4 studies not complying with inclusion criteria (1 robotic gastrecto versus open gastrectomy meta-analysis; 1 umbrella review; 1 umbrella review protoc network meta-analysis), 7 meta-analyses underwent qualitative synthesis [14][15][16][17][18][19][20]. No ditional record was found through other source (References list).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Table 1 shows demographic features of 7 included meta-analyses that covered 2000-2020 time frame [14][15][16][17][18][19][20]. Studies included into the meta-analyses ranged from 12 to 40, were almost all retrospective ones and originated from Asian countries (China and Korea, in particular) [14][15][16][17][18][19][20].…”
Section: General Population Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations